2022
DOI: 10.1136/bmjopen-2021-049630
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in demand satisfied with modern methods of family planning among women aged 15–49 years: a secondary data analysis of Demographic and Health Surveys of six South Asian countries

Abstract: ObjectiveTo estimate educational and wealth inequalities in demand satisfied with modern methods of family planning (mDFPS).DesignA secondary data analyses of Demographic and Health Surveys.SettingSix South Asian countries, Afghanistan (2015), Bangladesh (2014), India (2015–2016), Maldives (2016–2017), Nepal (2016) and Pakistan (2017–2018).ParticipantsWomen aged 15–49 years. Primary and secondary outcome measures mDFPS was defined as married women aged 15–49 years or their partners, who desired no child, no ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, the pace of improvement varies among subgroups and provinces. While progress has been made in closing the coverage gap, the trajectory of improvement appeared to have slowed down for demand satis ed by modern methods and care-seeking for pneumonia (21)(22)(23). Despite the improvements, persistent socioeconomic and urban-rural inequalities persist across the RMNCH service indicators, posing challenges to achieving universal health coverage in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pace of improvement varies among subgroups and provinces. While progress has been made in closing the coverage gap, the trajectory of improvement appeared to have slowed down for demand satis ed by modern methods and care-seeking for pneumonia (21)(22)(23). Despite the improvements, persistent socioeconomic and urban-rural inequalities persist across the RMNCH service indicators, posing challenges to achieving universal health coverage in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pace of improvement varies among subgroups and provinces. While progress has been made in closing the coverage gap, the trajectory of improvement appeared to have slowed down for demand satisfied by modern methods and care-seeking for pneumonia [ 22 24 ]. Despite the improvements, persistent socioeconomic and urban‒rural inequalities persist across the RMNCH service indicators, posing challenges to achieving universal health coverage in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…The following study covariates were used and selected based on previous studies, the PROGRESS framework [ 18 , 19 ], and data available in the ENSANUT-2018. For the assessment of inequalities, the variables used were age group (15 to 19 years, 20 to 29 years, 30 to 39, years, and 40 to 49 years) [ 7 , 9 , 20 ]; educational level (up to primary, secondary, higher) [ 6 , 7 ]; currently working (no, yes) [ 21 ]; ethnicity (“non-indigenous” for individuals who self-reported as afro-ecuatorian, white, mestizo, montubio, or others, and “indigenous” for those who self-reported as indigenous) [ 22 , 23 ]; and, area of residence (rural, urban). The following variables were used for the analysis of associated factors: age group (15 to 19 years, 20 to 29 years, 30 to 39, years, and 40 to 49 years) [ 7 , 9 , 20 ]; educational level (up to primary, secondary, higher) [ 21 ]; marital status (married, cohabiting) [ 10 ]; currently working (no, yes); parity (0 to 1, 2, 3 or more children) [ 24 , 25 ]; ethnicity (indigenous, non-indigenous) [ 23 ]; health insurance (yes, no) [ 26 ]; area of residence (rural, urban) [ 7 ]; region of residence (Highlands, Coast, Amazon, Island) [ 13 ]; and wealth quintile (“very poor”, “poor”, “medium”, “rich”, and “very rich”) [ 6 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported the presence of inequalities in the use of MCM according to certain population characteristics [ 6 , 7 , 8 , 9 , 10 , 11 ]. Thus, a study that included 11 low- and middle-income countries in the African and Asian regions identified inequalities in the satisfied demand for MCM in favor of women within the highest wealth quintile, those who were older, and women with higher levels of education [ 11 ].…”
Section: Introductionmentioning
confidence: 99%